Physiological constraints on heat adaptation in birds - Andreas Nord; Marc T. Freeman; Andrew E. McKechnie (Trends in Ecology & Evolution, 2026)

Towards cost-effective and sustainable PET recycling through glycolysis: Ethylene glycol recovery using solution-processable nanocomposite membranes - Hamidreza Mahdavi; Leonie van 't Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Chemical Engineering Journal, 2026)

The role of hyperthermia in avian tolerance of hot and humid conditions - Marc T. Freeman; Bianca Coulson; Celiwe A. Ngcamphalala; Mathome O. Makola; Andrew E. McKechnie (Journal of Thermal Biology, 2025)

Enhancing strategies for advanced treatment technologies to reduce microplastic pollution - Hamidreza Mahdavi; Suer Kurklu Kocaoglu; Laila Halim; Michael Batten; Abdollah Khosravanian; Leonie van ‘t Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Journal of Environmental Chemical Engineering, 2025)

Permeate fluxes from desalination of brines and produced waters: A reactive transport modeling study - Sergi Molins; Nicolas Spycher; Sarah M. Dischinger; Mostafa Nassr; Ji Yeon Lee; Jacob Johnston; Nils Tilton; Kristofer L. Gleason; Benny D. Freeman; William T. Stringfellow; Daniel J. Miller (Applied Geochemistry, 2025)

Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Jonathan H. Timperley; Brogan L. Pett; Bility Geninyan; Ari Saputra; Abraham Vincent; Romeo Weah; Benedictus Freeman; Marshall Guahn; Peter M. Hadfield; Morris T. Jah; Tiecanna Jones; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2025)

Metabolic gene expression differences in emaciated and moderately conditioned horses: RNA-seq analysis of postmortem skeletal muscle - M. Parr; E. Shepherd; M. Hines; L. Strickland; T. Freeman; S. Moisa; J. Beever; J. Ivey (Journal of Equine Veterinary Science, 2025)

Recent Abundance Changes at Species' Range Limits in the North and Central American Avifaunas - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Global Ecology and Biogeography, 2025)
Aim Species are often expected to track climate change via changes in their abundances and distributions. This climate tracking hypothesis generates the prediction that warming temperatures should cause species to show population increases at their poleward range limits and population decreases at their equatorward range limits. We tested these predictions for 516 species of North and Central American birds. Location North and Central America. Time Period 2012–2022. Major Taxa Studied Birds. Methods We used data on bird species' recent abundance changes within their breeding or year‐round distributions from eBird Status and Trends models, and temperature data from a global temperature dataset. We defined species' northern and southern range limits, then used regression models to test whether recent abundance changes at species' range limits were predicted by temperature change and a set of ecological traits. Results Abundance changes at species' range edges are not associated with temperature change. There is a latitudinal gradient in recent abundance changes: lower‐latitude species have increased in abundance at both northern and southern range limits, whereas higher‐latitude species have declined in abundance at both range limits. Conclusions Patterns of abundance change at species' northern and southern range limits are not consistent with the climate tracking hypothesis for North and Central American birds. This result casts doubt on the accuracy of long‐term biological forecasts that assume tight temperature tracking for these avifaunas. Our finding of a latitudinal gradient in recent abundance change suggests lower‐latitude species may generally be benefiting from climate change, with consequences for local and regional communities across latitudinal gradients.

Non-evaporative heat dissipation across the beaks and casques of large forest hornbills - Bianca Coulson; Marc T. Freeman; Juanita Wessels; Andrew E. McKechnie (Journal of Thermal Biology, 2024)

Heat tolerance and evaporative cooling capacity in an arid-zone elephant shrew - Olivia J. B. Chalwin-Milton; Marc T. Freeman; Andrew E. McKechnie (Mammalian Biology, 2024)
Endotherms vary widely in their capacity to defend sublethal body temperature ( T b ) during acute heat exposure. Interspecific variation in the upper thermal limits of small mammals remains poorly studied, particularly in taxa other than bats. We hypothesised that rupicolous elephant shrews (Macroscelidae), on account of their occupancy of above-ground rock crevices in hot habitats and rapid cursorial locomotion, have evolved pronounced heat tolerance capacities. To test this hypothesis, we quantified relationships between T b , resting metabolic rate (RMR) and evaporative water loss (EWL) in western rock elephant shrews ( Elephantulus rupestris ) exposed to air temperature ( T air ) approaching or exceeding T b under conditions of low humidity representative of the study population’s arid, winter-rainfall habitat in western South Africa. Our data revealed a pronounced capacity to tolerate T air > T b , with E. rupestris tolerating T air up to 48.0 ± 0.1 °C while defending T b > 7 °C below T air (maximum T b = 41.64 ± 0.16 °C). Three behavioural pathways were employed to dissipate heat: open mouth panting, flattening their body posture, and nose-licking. At the highest experimental T air values achieved, EWL increased 15.05-fold relative to normothermic levels and heat was dissipated evaporatively at rates equivalent to 174%—240% of metabolic heat production. The heat tolerance limit of T air = 48 °C in E. rupestris is one of the highest yet recorded in a non-volant small mammal, and our data support the notion that elephant shrews possess a pronounced capacity to avoid lethal hyperthermia during acute heat exposure.

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Effects of lead on avian thermoregulation in the heat: An experimental test with pied crows (Corvus albus) - Andrew E. McKechnie; Marc T. Freeman; Ryno Kemp; Kerri Wolter; Vinny Naidoo (Environmental Toxicology and Pharmacology, 2024)

Framework for assessing collection-based photocatalytic oxidation systems in HVAC applications for bioaerosol control - Sudharshan Anandan; Andrew J. Fix; Andrew J. Freeman; Lance Miller; Devon P. Scheg; Xavier Morgan; Jae Hong Park; William T. Horton; Ernest R. Blatchley; David M. Warsinger (Building and Environment, 2024)

Domestication and evolutionary histories of specialized gut symbionts across cephalotine ants - Christian Cabuslay; John T. Wertz; Benoît Béchade; Yi Hu; Sonali Braganza; Daniel Freeman; Shreyansh Pradhan; Maria Mukhanova; Scott Powell; Corrie Moreau; Jacob A. Russell (Molecular Ecology, 2024)
The evolution of animals and their gut symbionts is a complex phenomenon, obscured by lability and diversity. In social organisms, transmission of symbionts among relatives may yield systems with more stable associations. Here, we study the history of a social insect symbiosis involving cephalotine ants and their extracellular gut bacteria, which come predominantly from host‐specialized lineages. We perform multi‐locus phylogenetics for symbionts from nine bacterial orders, and map prior amplicon sequence data to lineage‐assigned symbiont genomes, studying distributions of rigorously defined symbionts across 20 host species. Based on monophyly and additional hypothesis testing, we estimate that these specialized gut bacteria belong to 18 distinct lineages, of which 15 have been successfully isolated and cultured. Several symbiont lineages showed evidence for domestication events that occurred later in cephalotine evolutionary history, and only one lineage was ubiquitously detected in all 20 host species and 48 colonies sampled with amplicon 16S rRNA sequencing. We found evidence for phylogenetically constrained distributions in four symbionts, suggesting historical or genetic impacts on community composition. Two lineages showed evidence for frequent intra‐lineage co‐infections, highlighting the potential for niche divergence after initial domestication. Nearly all symbionts showed evidence for occasional host switching, but four may, more often, co‐diversify with their hosts. Through our further assessment of symbiont localization and genomic functional profiles, we demonstrate distinct niches for symbionts with shared evolutionary histories, prompting further questions on the forces underlying the evolution of hosts and their gut microbiomes.

Interspecific competition shapes bird species' distributions along tropical precipitation gradients - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Ecology Letters, 2024)
The hypothesis that species' ranges are limited by interspecific competition has motivated decades of debate, but a general answer remains elusive. Here we test this hypothesis for lowland tropical birds by examining species' precipitation niche breadths. We focus on precipitation because it—not temperature—is the dominant climate variable that shapes the biota of the lowland tropics. We used 3.6 million fine‐scale citizen science records from eBird to measure species' precipitation niche breadths in 19 different regions across the globe. Consistent with the predictions of the interspecific competition hypothesis, multiple lines of evidence show that species have narrower precipitation niches in regions with more species. This means species inhabit more specialized precipitation niches in species‐rich regions. We predict this niche specialization should make tropical species in high diversity regions disproportionately vulnerable to changes in precipitation regimes; preliminary empirical evidence is consistent with this prediction.

Functional role of metabolic suppression in avian thermoregulation in the heat - Jochen J. Voges; Marc T. Freeman; Blair O. Wolf; Andrew E. McKechnie (Journal of Thermal Biology, 2024)

Internal and external factors affect pair mate proximity in captive coyotes, Canis latrans - Alexandra Turano; Stacey P. Brummer; Jeffrey T. Schultz; Julie K. Young; Sara M. Freeman (Animal Behaviour, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Evolution of avian heat tolerance: The role of atmospheric humidity - Marc T. Freeman; Bianca Coulson; James C. Short; Celiwe A. Ngcamphalala; Mathome O. Makola; Andrew E. McKechnie (Ecology, 2024)
The role of atmospheric humidity in the evolution of endotherms' thermoregulatory performance remains largely unexplored, despite the fact that elevated humidity is known to impede evaporative cooling capacity. Using a phylogenetically informed comparative framework, we tested the hypothesis that pronounced hyperthermia tolerance among birds occupying humid lowlands evolved to reduce the impact of humidity‐impeded scope for evaporative heat dissipation by comparing heat tolerance limits (HTLs; maximum tolerable air temperature), maximum body temperatures ( T b max), and associated thermoregulatory variables in humid (19.2 g H 2 O m −3 ) versus dry (1.1 g H 2 O m −3 ) air among 30 species from three climatically distinct sites (arid, mesic montane, and humid lowland). Humidity‐associated decreases in evaporative water loss and resting metabolic rate were 27%–38% and 21%–27%, respectively, and did not differ significantly between sites. Decreases in HTLs were significantly larger among arid‐zone (mean ± SD = 3.13 ± 1.12°C) and montane species (2.44 ± 1.0°C) compared to lowland species (1.23 ± 1.34°C), with more pronounced hyperthermia among lowland ( T b max = 46.26 ± 0.48°C) and montane birds ( T b max = 46.19 ± 0.92°C) compared to arid‐zone species (45.23 ± 0.24°C). Our findings reveal a functional link between facultative hyperthermia and humidity‐related constraints on evaporative cooling, providing novel insights into how hygric and thermal environments interact to constrain avian performance during hot weather. Moreover, the macrophysiological patterns we report provide further support for the concept of a continuum from thermal specialization to thermal generalization among endotherms, with adaptive variation in body temperature correlated with prevailing climatic conditions.

Comprehensive Analysis of Coal Combustion Characteristics and Kinetic Parameters of Botswana Coal, Morupule, Mmamabula and Mabesekwa Coalfields - Kamogelo P. Keboletse; Freeman Ntuli; Oluseyi P. Oladijo; Thato Mongalenyane; Gunvor M. Kirkelund; Ana T. Lima (Natural Resources Research, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Correction to: The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age‑matched controls - W. Lawn; N. Fernandez‑Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)

A novel technique for aging male African elephants (Loxodonta africana) using craniofacial photogrammetry and geometric morphometrics - Caitlin E. O’Connell-Rodwell; Patrick T. Freeman; Colleen Kinzley; Monica N. Sandri; Jodie L. Berezin; Maggie Wiśniewska; Kelsey Jessup; Timothy C. Rodwell (Mammalian Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Future climate risks from stress, insects and fire across US forests - William R. L. Anderegg; Oriana S. Chegwidden; Grayson Badgley; Anna T. Trugman; Danny Cullenward; John T. Abatzoglou; Jeffrey A. Hicke; Jeremy Freeman; Joseph J. Hamman (Ecology Letters, 2022)
Forests are currently a substantial carbon sink globally. Many climate change mitigation strategies leverage forest preservation and expansion, but rely on forests storing carbon for decades to centuries. Yet climate‐driven disturbances pose critical risks to the long‐term stability of forest carbon. We quantify the climate drivers that influence wildfire and climate stress‐driven tree mortality, including a separate insect‐driven tree mortality, for the contiguous United States for current (1984–2018) and project these future disturbance risks over the 21st century. We find that current risks are widespread and projected to increase across different emissions scenarios by a factor of >4 for fire and >1.3 for climate‐stress mortality. These forest disturbance risks highlight pervasive climate‐sensitive disturbance impacts on US forests and raise questions about the risk management approach taken by forest carbon offset policies. Our results provide US‐wide risk maps of key climate‐sensitive disturbances for improving carbon cycle modeling, conservation and climate policy.

The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age-matched controls - W. Lawn; N. Fernandez-Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)
Background Preclinical and human studies suggest that adolescent cannabis use may be associated with worse cognitive outcomes than adult cannabis use. We investigated the associations between chronic cannabis use and cognitive function in adolescent and adult cannabis users and controls. We hypothesised user-status would be negatively associated with cognitive function and this relationship would be stronger in adolescents than adults. Methods As part of the ‘CannTeen’ project, this cross-sectional study assessed cognitive performance in adolescent cannabis users ( n = 76; 16–17-year-olds), adolescent controls ( n = 63), adult cannabis users ( n = 71; 26–29-year-olds) and adult controls ( n = 64). Users used cannabis 1–7 days/week. Adolescent and adult cannabis users were matched on cannabis use frequency (4 days/week) and time since last use (2.5 days). Verbal episodic memory (VEM) was assessed using the prose recall task, spatial working memory (SWM) was assessed using the spatial n-back task, and response inhibition was assessed with the stop-signal task. Primary outcome variables were: delayed recall, 3-back discriminability, and stop signal reaction time, respectively. Results Users had worse VEM than controls ( F (1,268) = 7.423, p = 0.007). There were no significant differences between user-groups on SWM or response inhibition. Null differences were supported by Bayesian analyses. No significant interactions between age-group and user-group were found for VEM, SWM, or response inhibition. Conclusions Consistent with previous research, there was an association between chronic cannabis use and poorer VEM, but chronic cannabis use was not associated with SWM or response inhibition. We did not find evidence for heightened adolescent vulnerability to cannabis-related cognitive impairment.

Clinical withdrawal symptom profile of synthetic cannabinoid receptor agonists and comparison of effects with high potency cannabis - Sam Craft; Jason A. Ferris; Monica J. Barratt; Larissa J. Maier; Michael T. Lynskey; Adam R. Winstock; Tom P. Freeman (Psychopharmacology, 2022)
Synthetic cannabinoid receptor agonists (SCRAs) may be used as an alternative to natural cannabis; however, they may carry a greater risk of problematic use and withdrawal. This study aimed to characterise the withdrawal symptom profile of SCRAs and compare their profile of effect with high-potency herbal cannabis. Global Drug Survey data (2015 and 2016) were used to access a clinically relevant sample of people reporting use of SCRAs >10 times in the past 12-months, a previous SCRA quit attempt, and lifetime use of high-potency herbal cannabis. Participants completed an 11-item SCRA withdrawal symptom checklist and compared SCRAs and high-potency herbal cannabis on their onset and duration of effects, speed of the development of tolerance, severity of withdrawal, and difficulty with dose titration. Participants ( n = 284) reported experiencing a mean of 4.4 (95% CI: 4.1, 4.8) withdrawal symptoms after not using SCRAs for >1 day; most frequently reported were sleep issues (59.2%), irritability (55.6%), and low mood (54.2%). Withdrawal symptoms were significantly associated with frequency (>51 vs. 11–50 times per year: IRR = 1.43, 95% CI: 1.16, 1.77, p = 0.005) and quantity (grams per session: IRR = 1.13, 95% CI: 1.05, 1.22, p = 0.001) of SCRA use. Compared to high-potency herbal cannabis, SCRAs were rated as having a faster onset and shorter duration of effects, faster development of tolerance, and more severe withdrawal ( p ’s < 0.001). In conclusion, SCRA withdrawal symptoms are more likely to occur after greater SCRA exposure. The effects of SCRA indicate a more severe withdrawal syndrome and a greater risk of problematic use than natural cannabis.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The precautionary principle and dietary DNA metabarcoding: Commonly used abundance thresholds change ecological interpretation - Bethan L. Littleford‐Colquhoun; Patrick T. Freeman; Violet I. Sackett; Camille V. Tulloss; Lauren M. McGarvey; Chris Geremia; Tyler R. Kartzinel (Molecular Ecology, 2022)
Dietary DNA metabarcoding enables researchers to identify and characterize trophic interactions with a high degree of taxonomic precision. It is also sensitive to sources of bias and contamination in the field and laboratory. One of the earliest and most common strategies for dealing with such sensitivities has been to remove all low‐abundance sequences and conduct ecological analyses based on the presence or absence of food taxa. Although this step is now often perceived to be necessary, evidence of its sufficiency is lacking and more attention to the risk of introducing other errors is needed. Using computer simulations, we demonstrate that common strategies to remove low‐abundance sequences can erroneously eliminate true dietary sequences in ways that impact downstream inferences. Using real data from well‐studied wildlife populations in Yellowstone National Park, we further show how these strategies can markedly alter the composition of dietary profiles in ways that scale‐up to obscure ecological interpretations about dietary generalism, specialism, and composition. Although the practice of removing low‐abundance sequences may continue to be a useful strategy to address research questions that focus on a subset of relatively abundant foods, its continued widespread use risks generating misleading perceptions about the structure of trophic networks. Researchers working with dietary DNA metabarcoding data—or similar data such as environmental DNA, microbiomes, or pathobiomes—should be aware of drawbacks and consider alternative bioinformatic, experimental, and statistical solutions.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Systematic over‐crediting in California's forest carbon offsets program - Grayson Badgley; Jeremy Freeman; Joseph J. Hamman; Barbara Haya; Anna T. Trugman; William R. L. Anderegg; Danny Cullenward (Global Change Biology, 2022)
Carbon offsets are widely used by individuals, corporations, and governments to mitigate their greenhouse gas emissions on the assumption that offsets reflect equivalent climate benefits achieved elsewhere. These climate‐equivalence claims depend on offsets providing real and additional climate benefits beyond what would have happened, counterfactually, without the offsets project. Here, we evaluate the design of California's prominent forest carbon offsets program and demonstrate that its climate‐equivalence claims fall far short on the basis of directly observable evidence. By design, California's program awards large volumes of offset credits to forest projects with carbon stocks that exceed regional averages. This paradigm allows for adverse selection, which could occur if project developers preferentially select forests that are ecologically distinct from unrepresentative regional averages. By digitizing and analyzing comprehensive offset project records alongside detailed forest inventory data, we provide direct evidence that comparing projects against coarse regional carbon averages has led to systematic over‐crediting of 30.0 million tCO 2 e (90% CI: 20.5–38.6 million tCO 2 e) or 29.4% of the credits we analyzed (90% CI: 20.1%–37.8%). These excess credits are worth an estimated $410 million (90% CI: $280–$528 million) at recent market prices. Rather than improve forest management to store additional carbon, California's forest offsets program creates incentives to generate offset credits that do not reflect real climate benefits.

Multiscale Digital Rock Analysis for Complex Rocks - L. C. Ruspini; P. E. Øren; S. Berg; S. Masalmeh; T. Bultreys; C. Taberner; T. Sorop; F. Marcelis; M. Appel; J. Freeman; O. B. Wilson (Transport in Porous Media, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Quantification of observable behaviors induced by typical and atypical kappa-opioid receptor agonists in male rhesus monkeys - S. L. Huskinson; D. M. Platt; M. Brasfield; M. E. Follett; T. E. Prisinzano; B. E. Blough; K. B. Freeman (Psychopharmacology, 2020)

Mammalian tolerance to humans is predicted by body mass: evidence from long‐term archives - Jennifer J. Crees; Samuel T. Turvey; Robin Freeman; Chris Carbone (Ecology, 2019)
Humans are implicated as a major driver of species extinctions from the Late Pleistocene to the present. However, our predictive understanding of human‐caused extinction remains poor due to the restricted temporal and spatial scales at which this process is typically assessed, and the risks of bias due to “extinction filters” resulting from a poor understanding of past species declines. We develop a novel continent‐wide data set containing country‐level last‐occurrence records for 31 European terrestrial mammals across the Holocene (c.11,500 yr BP to present), an epoch of relative climatic stability that captures major transitions in human demography. We analyze regional extirpations against a high‐resolution database of human population density ( HPD ) estimates to identify species‐specific tolerances to changing HPD through the Holocene. Mammalian thresholds to HPD scale strongly with body mass, with larger‐bodied mammals experiencing regional population losses at lower HPD s than smaller‐bodied mammals. Our analysis enables us to identify levels of tolerance to HPD for different species, and therefore has wide applicability for determining biotic vulnerability to human impacts. This ecological pattern is confirmed across wide spatiotemporal scales, providing insights into the dynamics of prehistoric extinctions and the modern biodiversity crisis, and emphasizing the role of long‐term archives in understanding human‐caused biodiversity loss.

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Toxicity, recovery, and resilience in a 3D dopaminergic neuronal in vitro model exposed to rotenone - Georgina Harris; Melanie Eschment; Sebastian Perez Orozco; J. Michael McCaffery; Richard Maclennan; Daniel Severin; Marcel Leist; Andre Kleensang; David Pamies; Alexandra Maertens; Helena T. Hogberg; Dana Freeman; et al. (Archives of Toxicology, 2018)

Psilocybin with psychological support improves emotional face recognition in treatment-resistant depression - J. B. Stroud; T. P. Freeman; R. Leech; C. Hindocha; W. Lawn; D.J. Nutt; H.V Curran; R. L. Carhart-Harris (Psychopharmacology, 2018)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

Constructed wetlands may lower inorganic nutrient inputs but enhance DOC loadings into a drinking water reservoir in North Wales - C. Scholz; T. G. Jones; M. West; A. M. S. Ehbair; C. Dunn; C. Freeman (Environmental Science and Pollution Research, 2016)

The effects of nicotine dependence and acute abstinence on the processing of drug and non-drug rewards - W. Lawn; T. P. Freeman; C. Hindocha; C. Mokrysz; R. K. Das; C. J. A. Morgan; H. V. Curran (Psychopharmacology, 2015)

Field-Scale Simulation of Production from Oceanic Gas Hydrate Deposits - Matthew T. Reagan; George J. Moridis; Jeffery N. Johnson; Lehua Pan; Craig M. Freeman; Lehua Pan; Katie L. Boyle; Noel D. Keen; Jarle Husebo (Transport in Porous Media, 2015)

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Clostridium difficile as a cause of healthcare-associated diarrhoea among children in Auckland, New Zealand: clinical and molecular epidemiology - V. Sathyendran; G. N. McAuliffe; T. Swager; J. T. Freeman; S. L. Taylor; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A gastropod’s induced behavioral and morphological responses to invasive Carcinus maenas in Australia indicate a lack of novelty advantage - Aaren S. Freeman; Jeffrey T. Wright; Chad L. Hewitt; Marnie L. Campbell; Kaylene Szeto (Biological Invasions, 2013)

Breeding together: modeling synchrony in productivity in a seabird community - José J. Lahoz-Monfort; Byron J. T. Morgan; Michael P. Harris; Francis Daunt; Sarah Wanless; Stephen N. Freeman (Ecology, 2013)
With environmental conditions changing rapidly, there is a need to move beyond single‐species models and consider how communities respond to environmental drivers. We present a modeling approach that allows estimation of multispecies synchrony in productivity, or its components, and the contribution of environmental covariates as synchronizing and desynchronizing agents. We apply the model to long‐term breeding success data for five seabird species at a North Atlantic colony. Our Bayesian analysis reveals varying degrees of synchrony in overall productivity, with a common signal indicating a significant decline in productivity between 1986 and 2009. Productivity in seabirds reflects conditions in the marine ecosystem so the estimated synchronous component is a useful indicator of local marine environment health. For the two species for which we have most data, the environmental contribution to overall productivity synchrony is driven principally by effects operating at the chick stage rather than during incubation. Our results emphasize the importance of studying together species that coexist in a community. The framework, which accommodates interspecific clutch‐size variation, is readily applicable to any species assemblage in any ecosystem where long‐term productivity data are available.

Identification of Cys94 as the distal ligand to the Fe(III) heme in the transcriptional regulator RcoM-2 from Burkholderia xenovorans - Aaron T. Smith; Katherine A. Marvin; Katherine M. Freeman; Robert L. Kerby; Gary P. Roberts; Judith N. Burstyn (JBIC Journal of Biological Inorganic Chemistry, 2012)

Dealing With Uncertainty When Assessing Fish Passage Through Culvert Road Crossings - Gregory B. Anderson; Mary C. Freeman; Byron J. Freeman; Carrie A. Straight; Megan M. Hagler; James T. Peterson (Environmental Management, 2012)

Comparative epidemiology of CTX-M-14 and CTX-M-15 producing Escherichia coli: Association with distinct demographic groups in the community in New Zealand - J. T. Freeman; D. A. Williamson; H. Heffernan; M. Smith; J. E. Bower; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evidence for scent marking in vervet monkeys? - N. J. Freeman; G. M. Pasternak; T. L. Rubi; L. Barrett; S. P. Henzi (Primates, 2012)

High rates of susceptibility to ceftazidime among globally prevalent CTX-M-producing Escherichia coli: potential clinical implications of the revised CLSI interpretive criteria - D. A. Williamson; S. A. Roberts; M. Smith; H. Heffernan; A. Tiong; C. Pope; J. T. Freeman (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A Numerical Study of Microscale Flow Behavior in Tight Gas and Shale Gas Reservoir Systems - C. M. Freeman; G. J. Moridis; T. A. Blasingame (Transport in Porous Media, 2011)

Molecular diagnosis of Myxobolus spirosulcatus associated with encephalomyelitis of cultured yellowtail, Seriola quinqueradiata Temminck & Schlegel - H Yokoyama; T Yanagida; M A Freeman; T Katagiri; A Hosokawa; M Endo; M Hirai; S Takagi (Journal of Fish Diseases, 2010)
Mass mortality of cultured yellowtail, Seriola quinqueradiata , has recently been reported from fish farms in western Japan. Previous studies revealed that diseased fish were characterized by encephalomyelitis and presporogonic stages of a myxosporean‐like parasite in the spinal cord. However, the parasite has remained unidentified because of the lack of mature stages being present. Thus, in the present study, analysis of the small subunit ribosomal DNA (18S rDNA) of the parasite as well as in situ hybridization (ISH) studies using histological sections of the infected tissue was conducted. The 18S rDNA of the myxosporean had higher sequence similarities with those of bile‐duct‐infecting myxosporeans rather than those infecting nervous tissues and was identified as Myxobolus spirosulcatus . The ISH using specific probes demonstrated that the DNA amplified was derived from the multinuclear organisms found in histological sections. A highly sensitive and specific PCR‐based assay for M. spirosulcatus was developed, which revealed a high prevalence of infection in cultured yellowtail that exhibited the clinical signs of encephalomyelitis.

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Modeling the Relations Between Flow Regime Components, Species Traits, and Spawning Success of Fishes in Warmwater Streams - Scott W. Craven; James T. Peterson; Mary C. Freeman; Thomas J. Kwak; Elise Irwin (Environmental Management, 2010)

Cosmogenic nuclide exposure ages from the ‘Parallel Roads’ of Glen Roy, Scotland - Derek Fabel; David Small; Maria Miguens‐Rodriguez; Stewart P. H. T. Freeman (Journal of Quaternary Science, 2010)
The ‘Parallel Roads’ of Glen Roy, Scotland, are the shorelines of former ice‐dammed lakes created by the last glaciers to occupy the area. We use surface exposure dating with cosmic ray‐produced 10 Be in quartz to provide the first numerical age control on the timing of formation of one of one of these shorelines and depositional features in Glen Roy. Four bedrock samples from the surface of the 325 m ‘Parallel Road’ yielded a mean formation age of ca. 11.5–11.9 ka. This age range confirms the long‐held view that the ‘Parallel Roads’ are Loch Lomond Stadial (ca. 12.9–11.5 ka) features. The age range reflects variation in currently available cosmogenic nuclide scaling schemes and the related 10 Be production rates. Two samples from the surface of the Turret fan indicate that the 260 m lake drained before ca. 10.7–11.0 ka, while two samples from the Brunachan fan suggest that subaerial sedimentation occurred after ca. 9.7–9.9 ka. Copyright © 2009 John Wiley & Sons, Ltd.

Compressed History Matching: Exploiting Transform-Domain Sparsity for Regularization of Nonlinear Dynamic Data Integration Problems - Behnam Jafarpour; Vivek K. Goyal; Dennis B. McLaughlin; William T. Freeman (Mathematical Geosciences, 2010)

Population studies and conservation of Jamaica’s endangered swallowtail butterfly Papilio (Pterourus) homerus - Eric Garraway; A. J. A. Bailey; B. E. Freeman; J. R. Parnell; T. C. Emmel (Journal of Insect Conservation, 2008)

Evidence for a transposition event in a second NITR gene cluster in zebrafish - Jeffrey A. Yoder; John P. Cannon; Ronda T. Litman; Carly Murphy; Jennifer L. Freeman; Gary W. Litman (Immunogenetics, 2008)

The use of bromide and chloride mass ratios to differentiate salt-dissolution and formation brines in shallow groundwaters of the Western Canadian Sedimentary Basin - James T. Freeman (Hydrogeology Journal, 2007)

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Sand and nest temperatures and an estimate of hatchling sex ratio from the Heron Island green turtle (Chelonia mydas) rookery, Southern Great Barrier Reef - David T. Booth; Candida Freeman (Coral Reefs, 2006)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

Admixture and diversity in West African cattle populations - A. R. FREEMAN; C. M. MEGHEN; D. E. MacHUGH; R. T. LOFTUS; M. D. ACHUKWI; A. BADO; B. SAUVEROCHE; D. G. BRADLEY (Molecular Ecology, 2004)
We present a population genetic analysis of microsatellite variation in 16 West African cattle populations. West Africa represents a unique juxtaposition of different climatic and ecological zones in a relatively small geographical area. While more humid coastal regions are inhabited by the tsetse fly, a vector which spreads trypanosomiasis among cattle, the disease is not transmitted in the drier areas outside this zone. This is the most thorough study of genetic diversity in cattle within this area, which contains genetically important trypanotolerant Bos taurus breeds. Genetic relationships among the many breeds are examined and levels of diversity are assessed. Admixture levels were determined using a variety of methods. Ancestry informative or population‐associated alleles (PAAs) were selected using populations from India, the Near East and Europe. Multivariate analysis, the admix program and model‐based Bayesian admixture analysis approaches were also employed. These analyses reveal the direct impact of ecological factors and the profound effect of admixture on the cattle of this region. They also highlight the importance of efforts to prevent further dilution of African taurine breeds by B. indicus cattle.

Social pairing and female mating fidelity predicted by restriction fragment length polymorphism similarity at the major histocompatibility complex in a songbird - Corey R. Freeman‐Gallant; Michael Meguerdichian; Nathaniel T. Wheelwright; Suzanne V. Sollecito (Molecular Ecology, 2003)
Female birds often copulate outside the pair‐bond to produce broods of mixed paternity, but despite much recent attention the adaptive significance of this behaviour remains elusive. Although several studies support the idea that extra‐pair copulations (EPCs) allow females to obtain ‘good genes’ for their offspring, many others have found no relationship between female mating fidelity and traits likely to reflect male quality. A corollary to the good genes hypothesis proposes that females do use EPCs to increase the quality of young, but it is the interaction between maternal and paternal genomes — and not male quality per se — that is the target of female choice. We tested this ‘genetic compatibility’ hypothesis in a free‐living population of Savannah sparrows ( Passerculus sandwichensis ) by determining whether females mated nonrandomly with respect to the major histocompatibility complex ( Mhc ). During both the 1994 and 1995 breeding seasons, female yearlings (but not older birds) avoided pairing with Mhc ‐similar males ( P Mhc similarity between mates also predicted the occurrence of extra‐pair young in first broods ( P P = 0.007). The overall genetic similarity between adults tended to predict female mating fidelity, but with less precision than their Mhc similarity ( P = 0.09). In contrast, females appeared insensitive to the size, weight or age of males, none of which explained variation in female mating fidelity. Taken together, these results are consistent with the hypothesis that females sought complementary genes for their offspring and suggest either that the benefits of heterozygosity (at the Mhc ) drive female mating patterns or that the avoidance of inbreeding is an ultimate cause of social and genetic mate choice in Savannah sparrows.

Microsatellite primers indicate the presence of asexual populations ofVenturia inaequalis in coastal Israeli apple orchards - Eric W. A. Boehm; S. Freeman; E. Shabi; T. J. Michailides (Phytoparasitica, 2003)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Comparative analysis of the promoter regions and transcriptional start sites of mouse Ly49 genes - Brian T. Wilhelm; Karina L. McQueen; J. Douglas Freeman; Fumio Takei; Dixie L. Mager (Immunogenetics, 2001)

Sequence Heteroplasmy of D-Loop and rRNA Coding Regions in Mitochondrial DNA from Holstein Cows of Independent Maternal Lineages - Jianming Wu; Renotta K. Smith; A. E. Freeman; Donald C. Beitz; Ben T. McDaniel; Gary L. Lindberg (Biochemical Genetics, 2000)

Cell-specific activation of the HB-EGF and ErbB1 genes by stretch in primary human bladder cells - Hiep T. Nguyen; John M. Park; Craig A. Peters; Rosalyn M. Adam; Anna Orsola; Anthony Atala; Michael R. Freeman (In Vitro Cellular & Developmental Biology - Animal, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Survey of Grauer's Gorillas (Gorilla gorilla graueri) and Eastern Chimpanzees (Pan troglodytes schweinfurthi) in the Kahuzi-Biega National Park Lowland Sector and Adjacent Forest in Eastern Democratic Republic of Congo - Jefferson S. Hall; Lee J. T. White; Bila-Isia Inogwabini; Ilambu Omari; Hilary Simons Morland; Elizabeth A. Williamson; Kristin Saltonstall; Peter Walsh; Claude Sikubwabo; Dumbo Bonny; Kaleme Prince Kiswele; Amy Vedder; et al. (International Journal of Primatology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Extra-pair paternity in tree swallows: why do females mate with more than one male? - Peter O. Dunn; Raleigh J. Robertson; Denise Michaud-Freeman; Peter T. Boag (Behavioral Ecology and Sociobiology, 1994)

Extra-pair paternity in tree swallows: why do females mate with more than one male? - P. O. Dunn; Raleigh J. Robertson; Denise Michaud-Freeman; Peter T. Boag (Behavioral Ecology and Sociobiology, 1994)

A histopathological examination of, and analysis for polychlorinated hydrocarbons in, inshore Atlantic cod (Gadus morhua) - H. C. Freeman; G. B. Sangalang; J. F. Uthe; E. T. Garside; P. G. Daye (Archives of Environmental Contamination and Toxicology, 1983)

Uptake, depuration, and distribution of selenium inDaphnia and its effects on survival and ultrastructure - T. Wayne Schultz; Scott R. Freeman; James N. Dumont (Archives of Environmental Contamination and Toxicology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Suberization and periderm development in Norchief and Red Pontiac potatoes - S. A. Ali; D. C. Nelson; T. P. Freeman (American Journal of Potato Research, 1975)

Physiological and storage problems number - H. S. Yohe; Wm. Stuart; C. O. Appleman; John Bushnell; Julian A. Dimock; J. T. Rosa; Earl S. Johnston; E. P. Miller; Freeman Weiss (American Journal of Potato Research, 1925)